Modelling the effect of drilled cuttings on the rheological properties of waste vegetable oil biodiesel in water based drilling mud. Issue 6 (2nd November 2017) - Tchameni, Alain P.; Zhao, Lin; Nagre, Robert D.; Ma, Chao
Abstract: This work compares the experimental results of the effects of drilled shale on the formulated oil-in-water emulsion drilling mud using biodiesel produced from waste vegetable oil (WVO) with white oil 5# at 140 °C. The concentration of drilled shale with particle sizes distribution between 80 and 100 mesh was varied from 0 to 16 wt./vol.%. The plastic viscosity, yield point, thixotropy, high-temperature–high-pressure (HTHP) filtration loss, coefficient of friction, and rate of drilled cuttings recovery were assessed. The biodiesel-in-water emulsion drilling mud (BEDM) exhibited better rheological behavior and stability compared to white oil-in-water emulsion drilling mud (WEDM) under the different conditions examined. BEDM demonstrated the lowest HTHP filtration volume with values ranging from 6 to13 cm 3 compared to WEDM with 9–18 cm 3 and water-based mud (WBM) of 12–25 cm 3 . Moreover, coefficients of friction of BEDM, WEDM, and WBM were 0.26, 0.35, and 0.75, respectively. BEDM had the highest drilled cuttings recovery rate of 79.60%, followed by WEDM with a rate of 72.80%, while WBM recorded the least (46.25%). Hence, the use of WVO biodiesel as additive in water-based mud can enhance the drilled shale tolerance of water-based drilling mud in an environmentally friendly manner.